Radiation-Induced Polymerization of Polymethacrylic Gel for Dosimetry - Mustafa, Iskandar Shahrim (2006)
The aim of the present work is to investigate the effect of radiation on methacrylic acid (MAA) crosslinked with N, N’-methylene-bisacrylamide (BIS) for the purpose of developing a polymer gel dosimeter, namely, polymethacrylic gel (PMAAG). PMAAG of different concentrations of MAA and BIS were irradiated with the absorbed doses ranging from 0 Gy to 19 Gy. Using Raman spectrophotometer, five peak intensities were identified and represents the assigned bonding for C=C (2238 cm-1) of MAA, C=C (1634 cm-1) of BIS, C-C (2110 cm-1) of PMAA, C=O (1795 cm-1) of PMAA, CH2 (2905 cm-1) of PMAA, which have strong modes of vibration in the band positions. The Raman peak intensity y as a function of absorbed dose D was found to have a monoexponential expression in the form;   −+=−010DDeAyy. The dose sensitivity D0 and half dose D1/2 were obtained and found to increase with the concentrations of MAA monomer and BIS crosslinker. The dose correlation factor of BIS, kBIS is always higher than kMAA of MAA (kBIS > kMAA) for all C-C, C=C, C=O and CH2 stretching modes, indicating BIS is a very significant parameter in the polymerization process. Additionally, a Nuclear magnetic resonance (NMR) spectrometer was used in order to measure the relaxation time of polymethacrylic (PMAA) gel dosimeters. The relaxation rate (ΔR2) dose sensitivity value (12.5 + 0.1 Gy) of MAA monomer by Lepage, et al 2001 is comparable with PMAAG experimental value gained which are 12.6 + 0.1 Gy. A comparison between and indirect measurements of polymer formed along with consumptions of monomer and crosslinker are also obtained from this experimental work. Finally, a UV-Vis spectrophotometer was used to records PMAAG degree of absorption in order to determine the accuracy of PMAAG. The PMAAG has a mean value of absorption of 0.614 at 375 nm. The dose derived from PMAAG is comparable to Fricke dosimeter and ionization chamber readings between 4.7 ± 0.1% and 11.6 ± 0.1%. The dose errors of less than 10 ± 0.1% are considered acceptable in radiation processing, an improvement of accuracy less than 5.0 ± 0.1% is acceptable in radiotherapy.